Analysis of critical factors influencing the management of green supply chain practice in small and medium enterprises. Issue 2 (2017) - Choudhary, Aparna; Mondal, Sandeep; Mukherjee, Kampan
Increasing concern towards environment has forced the manufacturing firms to adopt and manage green supply chain practice (GSCP) in their business processes. The purpose of this paper is to explore the critical factors for managing GSCP in small and medium enterprises (SMEs), and establish contextual relationship among them. A list of 29 constructs influencing the management of GSCP was identified through extensive literature review and discussion with a panel of experts. A questionnaire based survey was conducted on 162 SMEs. Applying factor analysis, constructs were summarised into eight critical factors. Interpretive structural modelling (ISM) methodology was deployed to develop a structural model of these factors. Matrices' Impacts Cruises-Multiplication Appliqué a un Casement (MICMAC) analysis was done to classify the factors into different groups based on their driving and dependence power. Government regulation and support, organisational resources and capabilities, and top management commitment are vital for the SMEs in managing GSCP.